HR Strategy in Improving the Organizational Performance of Small Company - Chandra Fitra Arifianto; Nanda Gustian (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
Human resource management (HRM) practices in small businesses are often perceived as informal and less in line with normative HRM standards developed in the context of large organizations. This study aims to analyze how HRM practices are implemented in small businesses and to understand their role in addressing resource limitations and uncertain business environments. This study uses a qualitative approach with a case study design, collecting data through in-depth interviews and observations of business owners and employees. Data analysis was conducted thematically to identify patterns of HRM practices, including recruitment and selection, training and development, compensation, performance appraisal, and employment relations. The results of this study indicate that all HRM practices are carried out informally, flexibly, and highly dependent on business owner policies and daily operational needs. This finding strengthens the contingency and institutional perspectives in HRM by emphasizing the importance of organizational context in assessing the effectiveness of HRM practices. This study contributes to the HRM literature by redefining informality not as a deviation from ideal practices, but as a functional strategy relevant to small businesses, and provides practical implications for the development of more contextual and sustainable HRM.